Impacts of an active travel intervention with a cycling focus in a suburban context: One-year findings from an evaluation of London's in-progress mini-Hollands programme. (May 2019) - Aldred, Rachel; Croft, Joseph; Goodman, Anna
Highlights: Paper reports one-year findings from a longitudinal study of London 'mini-Hollands'. Interventions were associated with increased likelihood of any past-week cycling. Interventions were associated with increased past-week active travel time. They were associated with perceived improvements to cycling and street environments. No evidence either way of change in car use associated with interventions. Abstract: Background: More evidence is needed on the impacts of building infrastructure for walking and cycling. A knowledge gap and an implementation gap have been mutually reinforcing. This paper reports on a longitudinal study examining the impacts of the still in progress 'mini-Hollands programme', which seeks to transform local environments for walking and cycling, in three Outer London boroughs. Compared to Inner London, Outer London has low levels of cycling and low levels of walking, and is relatively car dependent. Methods: We conducted a longitudinal study of 1712 individuals sampled from households in mini-Holland boroughs (intervention sample) and from non mini-Holland Outer London boroughs (control sample). The intervention sample was further divided, a priori, into those living in "high-dose neighbourhoods", where substantial changes to the local walking and cycling infrastructure had been implemented, versus "low-dose neighbourhoods" where such improvements had not (yet) been made. At both baseline (2016) and one-year follow-up (2017), we administered an online survey of travel behaviour and attitudes to transport and the local environment. Results: One year's worth of interventions was associated with an increase in active travel among those living in areas defined as 'high-dose' neighbourhoods. Specifically, those in high-dose areas were 24% more likely to have done any past-week cycling at follow-up, compared to those living in non mini-Holland areas (95% CI, 2% to 52%). The mid-point estimate for increase in active travel (walking plus cycling) time for the same group was an additional 41.0 min (95% CI 7.0, 75.0 min). Positive changes in views about local environments were recorded in intervention areas, driven by a perceived improvement in cycling-related items. Controversy related to the interventions is expressed in a growth in perceptions that 'too much' money is spent on cycling in intervention areas. However, intervention areas also saw a reduction in perceptions that 'too little' money is spent (the latter view being common both at baseline and Wave 1 in control areas). Conclusion: Overall, the findings here suggest that programme interventions, while controversial, are having a measurable and early impact on active travel behaviour and perceptions of the local cycling environment.